2022
DOI: 10.1002/1873-3468.14506
|View full text |Cite
|
Sign up to set email alerts
|

On the role of ubiquinone in the proton translocation mechanism of respiratory complex I

Abstract: Complex I converts oxidoreduction energy into a proton electrochemical gradient across the inner mitochondrial or bacterial cell membrane. This gradient is the primary source of energy for aerobic synthesis of ATP. Oxidation of reduced nicotinamide adenine dinucleotide (NADH) by ubiquinone (Q) yields NAD + and ubiquinol (QH 2 ), which is tightly coupled to translocation of four protons from the negatively to the positively charged side of the membrane. Electrons from NADH oxidation reach the iron-sulfur centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Studies of the structure and kinetics of the electron transfer chain performed with X-ray diffraction and cryo-EM have confirmed that the ND1 channel is already a very tight fit for CoQ10 ( 27 ), as well as indicating two stable binding positions for CoQ10 within the tunnel, with perhaps only one close enough to N2 for effective e-transfer ( 28 ). Further, refined investigations with cryo-EM and X-ray crystallography performed on the mutant complex with CoQ10 will possibly provide supporting evidence of the distance of the CoQ10 head group to the N2 FeS cluster.…”
Section: Discussionmentioning
confidence: 97%
“…Studies of the structure and kinetics of the electron transfer chain performed with X-ray diffraction and cryo-EM have confirmed that the ND1 channel is already a very tight fit for CoQ10 ( 27 ), as well as indicating two stable binding positions for CoQ10 within the tunnel, with perhaps only one close enough to N2 for effective e-transfer ( 28 ). Further, refined investigations with cryo-EM and X-ray crystallography performed on the mutant complex with CoQ10 will possibly provide supporting evidence of the distance of the CoQ10 head group to the N2 FeS cluster.…”
Section: Discussionmentioning
confidence: 97%
“…15 Å from the N2 FeS cluster, which will drop the electron transfer rate to hundreds of microseconds (Figure S8E, Tables S5-S7). The latter site most likely prevents the reverse electron transfer(3739), and thus enhances the rate of forward reaction of complex I. Alternatively, it has been suggested based on structural data that more than one Q molecules can occupy the Q tunnel(32) and complex I may function with the involvement of two Q molecules with a redox reaction between them(40). To further probe the electron distribution for each complex type in this alternative experimental setting, we created additional QM/MM setups with two quinone molecules modeled in the Q tunnel (see Materials and Methods).…”
Section: Enhanced Catalytic Activity Of CI In Cold-induced Respirator...mentioning
confidence: 99%
“…Alternatively, it has been suggested based on structural data that more than one Q molecules can occupy the Q tunnel (32) and complex I may function with the involvement of two Q molecules with a redox reaction between them (40). To further probe the electron distribution for each complex type in this alternative experimental setting, we created additional QM/MM setups with two quinone molecules modeled in the Q tunnel (see Materials and Methods).…”
Section: Enhanced Catalytic Activity Of CI In Cold-induced Respirator...mentioning
confidence: 99%
“…Complex I receives two electrons from NADH (generated in the Krebs cycle and the beta-oxidation pathway) via a flavin mononucleotide (FMN) and transfers them along a chain of seven iron–sulphur centres to the reduction site where CoQ10 is reduced to ubiquinol. At the same time, this reaction is coupled with the pumping of four protons across the inner mitochondrial membrane and into the intermembrane space; thus, Complex I is a major contributor to the proton motive force driving ATP synthesis (Wikstrom et al, 2023) [ 3 ]. Complex II catalyses the oxidation of succinate to fumarate in the Krebs cycle, with the concomitant transfer of electrons from succinate to ubiquinone to form ubiquinol.…”
Section: The Ubiquinone–ubiquinol Redox Cyclementioning
confidence: 99%